Analytical solutions in rotating linear dilaton black holes: Resonant frequencies, quantization, greybody factor, and Hawking radiation - Sakalli, I. (Amer Physical Soc, 2016)
Charged massive scalar field perturbations are studied in the gravitational, electromagnetic, dilaton, and axion fields of rotating linear dilaton black holes. In this geometry, we separate the covariant Klein-Gordon equation into radial and angular parts and obtain the exact solutions of both the equations in terms of the confluent Heun functions. Using the radial solution, we study the problems of resonant frequencies, entropy/area quantization, and greybody factor. We also analyze the behavior of the wave solutions near the event horizon of the rotating linear dilaton black hole and derive its Hawking temperature via the Damour-Ruffini-Sannan method.
Keywords: Quasi-Normal Modes; Klein-Gordon Equation; Absorption Cross-Section; Particle-Emission Rates; Scalar Field; Massless Particles; Perturbations; Geometry; Spectrum; Energy